2003
DOI: 10.1029/2003jd003682
|View full text |Cite
|
Sign up to set email alerts
|

Rayleigh lidar observations of quasi‐sinusoidal waves in the tropical middle atmosphere

Abstract: [1] Rayleigh lidar observations of temperature for $2-7 hours on 38 nights during the period of 18 January-5 March 1999 and for $3 hours on 29 nights during 29 February-2 April 2000 in the altitude region of 27-60 km over Gadanki (13.5°N, 85°E) clearly show the dominance of the quasi-sinusoidal waves of periods in the range of $6-13 hours in temperature in the tropical middle atmosphere. During 1999, the vertical wavelength of these waves ranges from 7.1 to 17 km with a mean value of 12.0 ± 2.4 km while durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…Using these vertical wavelengths, the associated horizontal wavelengths of 0.5–1 hour and 2–4 hour period gravity waves are found to be between ∼500–1000 km and ∼500–3000 km respectively. Earlier studies using Rayleigh lidar over this latitude have shown that quasi‐sinusoidal gravity waves of periods in the range ∼6–13 hours with vertical wavelength of 7.1–17 km and horizontal wavelengths of ∼1000–3000 km are dominant in the tropical middle atmosphere [ Rajeev et al , 2003]. There are theoretical studies showing that for a range of frequencies commonly observed in vigorous convection, dominant vertical wavelengths of generated gravity waves is approximately twice the depth of the heating region and it is independent of the horizontal scale of the heating and frequency of the heating [ Beres et al , 2004].…”
Section: Resultsmentioning
confidence: 99%
“…Using these vertical wavelengths, the associated horizontal wavelengths of 0.5–1 hour and 2–4 hour period gravity waves are found to be between ∼500–1000 km and ∼500–3000 km respectively. Earlier studies using Rayleigh lidar over this latitude have shown that quasi‐sinusoidal gravity waves of periods in the range ∼6–13 hours with vertical wavelength of 7.1–17 km and horizontal wavelengths of ∼1000–3000 km are dominant in the tropical middle atmosphere [ Rajeev et al , 2003]. There are theoretical studies showing that for a range of frequencies commonly observed in vigorous convection, dominant vertical wavelengths of generated gravity waves is approximately twice the depth of the heating region and it is independent of the horizontal scale of the heating and frequency of the heating [ Beres et al , 2004].…”
Section: Resultsmentioning
confidence: 99%
“…These observations suggested that IGWs in the TLS have typical horizontal wavelengths of 200-2000 km, vertical wavelengths of 2-10 km, and intrinsic frequencies of 2-5 f (where f is the inertial frequency). In the upper stratosphere and mesosphere/lower thermosphere (MLT), IGWs were reported from lidar [Collins et al, 1994;Hu et al, 2002;Rajeev et al, 2003;Xu et al, 2006;Li et al, 2007Li et al, , 2010Lu et al, 2009Lu et al, , 2015aLu et al, , 2015bLu et al, , 2017Chen et al, 2013Chen et al, , 2016Cai et al, 2014;Baumgarten et al, 2015] and radar [Muraoka et al, 1987;Yamamoto et al, 1987;Gavrilov et al, 2000;Zhou and Morton, 2006;Nicolls et al, 2010;Chen et al, 2011Chen et al, , 2014Chen et al, , 2015Suzuki et al, 2013] measurements. These observations indicate that most IGWs in the MLT evidently exhibited a quasi-monochromatic feature.…”
Section: Introductionmentioning
confidence: 99%
“…As a delicate method, hodograph technique is extensively utilized to extract the predominant inertia–gravity wave (IGW) from the observational profiles of radiosonde (Huang et al., 2018; Tsuda et al., 1994; Vincent & Alexander, 2000; Yamamori & Sato, 2006; S. D. Zhang & Yi, 2005; S. D. Zhang et al., 2012, 2017), radar (Gavrilov et al., 2000; Nicolls et al., 2010; Suzuki et al., 2013; M. Yamamoto et al., 1987; Zhou & Morton, 2006), and lidar (Cai et al., 2014; Chen et al., 2013, 2016; Collins et al., 1994; Hu et al., 2002; T. Li et al., 2007; Lu et al., 2015, 2017; Rajeev et al., 2003; Xu et al., 2006). Combined with Doppler shifting equation, this technique can estimate the temporal and spatial parameters of quasi‐monochromatic IGW, such as wave period, wavelength, and propagation direction.…”
Section: Introductionmentioning
confidence: 99%